COVID-19 syndemic in Africa upto november 2021 - Mora-Alvarado, Darner A. (2022)
The present study shows the evolution of COVID-19 in the 54 African countries up to November 2021. The main aim is to determine the evolution of the new infections and deaths related to COVID-19 that occur in the continent and its comparison with the rest of the world. The study analysed available data from online sources, e.g. “Statista”, John Hopkins University, and WHO. Additionally, the study analysed the vaccination progress by continent identifying strengths and weaknesses for managing the health crisis provoked by SARS-CoV-2. Despite the forecast made by the WHO and other heath institutes results show Africa in the fourth place above Oceania. Lastly, this study recommends a deeper analysis of the COVID-19 epidemy in Africa and its comparison with the rest of the world.